2023
DOI: 10.54058/saheljvs.v20i1.373
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography following Castration, Otectomy and Gastrotomy in ‎Nigerian Indigenous Dogs

Abstract: Infrared thermography analyzes changes in the surface temperature of the skin and has been used in companion animals to identify inflammatory processes, neoplasia, pain, and neuropathies. This study evaluated and compared surgical wound surface temperatures in Nigerian Indigenous Dogs (NID). Nigerian indigenous dogs are a medium-sized breed that weighs between 8 to 30 kg with moderate hair length, and a mesocephalic cranial index. The dogs were randomly allocated into groups A, B, and C for castration, otectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Aside from castration, other invasive procedures, such as otectomy and gastrotomy, have been evaluated using the superficial temperature of the surgical wound. Saidu et al [ 107 ] evaluated the temperature of surgical wounds in indigenous dogs subjected to castration, otectomy, and gastrotomy, registering increases within the first 12 h post-surgery (+2.34 °C, +0.58 °C, and +0.56 °C, respectively), and, at 48 h, the temperature in the first two groups was higher than those undergoing gastrotomy. Accordingly, the authors concluded that increased values could be associated with pain and inflammatory responses, an effect that was not observed in gastrotomy.…”
Section: Irt As An Assistance Tool In Invasive and Surgical Proceduresmentioning
confidence: 99%
“…Aside from castration, other invasive procedures, such as otectomy and gastrotomy, have been evaluated using the superficial temperature of the surgical wound. Saidu et al [ 107 ] evaluated the temperature of surgical wounds in indigenous dogs subjected to castration, otectomy, and gastrotomy, registering increases within the first 12 h post-surgery (+2.34 °C, +0.58 °C, and +0.56 °C, respectively), and, at 48 h, the temperature in the first two groups was higher than those undergoing gastrotomy. Accordingly, the authors concluded that increased values could be associated with pain and inflammatory responses, an effect that was not observed in gastrotomy.…”
Section: Irt As An Assistance Tool In Invasive and Surgical Proceduresmentioning
confidence: 99%
“…The results showed that graft adherence and healing were obtained when neovascularization caused a similar temperature between the graft site and surrounding healthy tissue [ 84 ]. Similarly, in Nigerian indigenous dogs, IRT was used in animals undergoing castration, otectomy, and gastrotomy [ 87 ]. The authors evaluated wound surface temperature and found that the initial temperature of castrated dogs was 33.34 ± 0.86 °C, a temperature that increased to 35.64 ± 0.57 °C at 6 h postsurgery, 35.14 ± 0.38 at 24 h, 35.82 ± 0.61 °C at 48 h, 35.24 ± 0.64 at 1 week, and progressively decreased in the second week postsurgery (32.84 ± 1.27 °C).…”
Section: Infrared Thermography Used To Monitor Healing and Surgical W...mentioning
confidence: 99%
“…These studies, apart from showing that IRT can help to determine a sustained inflammatory response associated with healing delay, show that it is a tool that can help to refine current procedures not only because they are painful but because tissue damage might be greater with a greater inflammatory response. For example, analgesic options such as lidocaine in surgical incisions were evaluated through IRT to assess if the local anesthetic has a negative effect on wound healing, as studied in cats and dogs by Herlofson et al [ 87 ]. Surface temperatures between lidocaine alone or NaCl did not differ ( p = 0.554) with healing scores of 3 and 2.5, respectively, showing that lidocaine addition does not influence wound healing.…”
Section: Infrared Thermography Used To Monitor Healing and Surgical W...mentioning
confidence: 99%